Acyclic nucleoside bisphosphonates: synthesis and properties of chiral 2-amino-4,6-bis[(phosphonomethoxy)alkoxy]pyrimidines - Doláková, Petra; Dracínský, Martin; Masojídková, Milena; Solínová, Veronika; Kasicka, Václav; Holý, Antonín (European journal of medicinal chemistry, 2009)
2-Amino-4,6-bis[(phosphonomethoxy)alkoxy]pyrimidines bearing two equal or different achiral or chiral phosphonoalkoxy chains have been prepared either by aromatic nucleophilic substitution of 2-amino-4,6-dichloropyrimidine or by alkylation of 4,6-dihydroxy-2-(methylsulfanyl)pyrimidine with appropriate phosphonate-bearing building block. Alkylation of 4,6-dihydroxy-2-(methylsulfanyl)pyrimidine proved to be the method of choice for efficient preparation of variety of bisphosphonates. The enantiomeric purity of selected compounds was determined by capillary electrophoresis. Antiviral activity of bisphosphonates is discussed.
Keywords: stereoizomerie; Drug Screening Assays, Antitumor; Humans; HeLa buňky; pyrimidiny; Structure-Activity Relationship; vztahy mezi strukturou a aktivitou; Nucleosides; nukleosidy; Electrophoresis, Capillary; alkylace; Alkylation; lidé; zvířata; proliferace buněk; myši; molekulární struktura; Stereoisomerism; elektroforéza kapilární; Mice; Molecular Structure; HL-60 Cells; HeLa Cells; antivirové látky; Cell Proliferation; HL-60 buňky; Antiviral Agents; screeningové testy protinádorových léčiv; nádorové buněčné linie; Animals; Cell Line, Tumor; Pyrimidines; bisfosfonáty; Diphosphonates